your own question, for FREE!
solving with substitution
Join the QuestionCove community and study together with friends!
easier if you write the second equation as
\[x=y+9\] then substitute in the first to get
-x=-y-9 --> x = y+9
from (2) you get x=y+9
in (1) y+9+y=11
satellite meant \[2y+9=11\] on his second line. But the answer remains the same :)
Can't find your answer?
Make a FREE account and ask your own questions, OR help others and earn volunteer hours!
Join our real-time social learning platform and learn together with your friends!
3 hours ago
4 hours ago